Metadata schema for the GENNOVATE dataset and ways forward - Kruseman, Gideon; Lopez, Diana E.; Muchiri, Caroline; Lecoutere, Els (2024)
Introduction Why make qualitative data FAIR? Why make gender data FAIR? GENNOVATE